Characteristics and Antibacterial Properties of Film Membrane of Chitosan-Resveratrol for Wound Dressing - Basri A. Gani; Nur Asmah; Cut Soraya; Dharli Syafriza; Sri Rezeki; Muhammad Nazar; Subhaini Jakfar; Nurtami Soedarsono (Ital Publication, 2023)
The research aimed to evaluate the film membrane of Nano Chitosan Resveratrol (NCHR) for biological, physicochemical, and antibacterial properties. Psychochemically, the functional groups of chitosan compounds were examined by FTIR, chemical compounds by GCMS, and the morphology of chitosan and chemical elements by SEM-EDS. Biologically, the characteristics of NCHR were examined by solubility, swelling, permeability, and biodegradation tests. Meanwhile, the antibacterial properties were examined for inhibition of Porphyromonas gingivalis (P. gingivalis) ATCC 33277 by Minimal inhibition concentration (MIC) and growth assessment by spectrophotometry. Nano Chitosan (NCH) has appeared at 1033.85 cm-1 as a sharp peak indicating the P=O group and contains anti-toxicity compounds (Ethane, 1,1-diethoxy- (CAS) 1,1-Diethoxye) is 81.06% and antioxidant compounds Limonene is (1.28%). In addition, NCH has chemical elements, Oxygen Weight (69.4%), calcium (19.7%), magnesium (6.6%), and phosphorus (4.3%). NaCl 0.9%, PBS, and Aquades. In addition, it has an excellent index of water vapor transmission rate (WVTR) in all solvents (R2³ 0.95). The NCHR membrane film is bacteriostatic (≤ 300 CFU/mL) with each value of Minimal Inhibition Concentration (MIC) >15 mm. The Nano chitosan contains antitoxic, antioxidant, and antibacterial compounds with high oxygen elements. The film membrane of nano chitosan resveratrol can maintain the stability of changes in pH with a very high solubility index, swelling index, and WVTR index, as well as good biodegradation and antibacterial properties. Doi: 10.28991/ESJ-2023-07-03-012 Full Text: PDF